2017
DOI: 10.1177/2010105817716184
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ginkgo biloba and psycho-education on stress, anxiety and fatigue among refugees

Abstract: Background: Refugees and war survivors are at higher risk of developing mental health disorders. Anxiety and stress are caused by many factors, including a stressful environment that could cause fatigue and low quality of life. Despite the existence of many synthetic anxiolytic and antidepressant drugs, symptom management has still not been successful. Ginkgo biloba extract has been used as one of the potential herbal remedies to enhance cognitive functions. Psycho-education plays a significant role in allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A recent RCT found that a botanical product containing cistanche and ginkgo extracts improved ME/CFS symptoms [195]. Ginkgo is an antioxidant that improves memory and cognitive deficits and alleviates psychological and physiological distress and fatigue in subjects with mental health disorders [196]. Cistanche is a popular dietary ingredient in Chinese traditional medicine shown to delay the onset of fatigue [197].…”
Section: Supplementationmentioning
confidence: 99%
“…A recent RCT found that a botanical product containing cistanche and ginkgo extracts improved ME/CFS symptoms [195]. Ginkgo is an antioxidant that improves memory and cognitive deficits and alleviates psychological and physiological distress and fatigue in subjects with mental health disorders [196]. Cistanche is a popular dietary ingredient in Chinese traditional medicine shown to delay the onset of fatigue [197].…”
Section: Supplementationmentioning
confidence: 99%
“…In older adult patients with cognitive impairment, EGb761 enhances emotional function and stabilizes mood. 35,63,64 EGb761 has also been demonstrated to alleviate anxiety symptoms in adults with mental illness, even in younger patients with anxiety symptoms. The chemical structures and synergy of various chemical components found in EGb761 can produce neuroprotective effects, which are mediated by antioxidant effects and the regulation of neurotransmission, neuroendocrine signaling, and neurotrophic factors, resulting in the relief of anxiety symptoms.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…[107] EGb has been reported to reduce anxiety and stress disorders, particularly in elderly patients with a cognitive decline, by improving brain neurotransmitters. [112] In the COVID-19 era, with substantial development of anti-SARS-CoV-2 vaccines, antibody titers postvaccination, however, may not be persistent in immune-comprised patients. Thus, it is suggested that some patients whose antibody titers diminish more rapidly than in healthy individuals will need a booster (comparable with hepatitis B vaccination).…”
Section: Sars-cov-2 Infection Is Linked With the Development Of Variousmentioning
confidence: 99%
“…[ 107 ] EGb has been reported to reduce anxiety and stress disorders, particularly in elderly patients with a cognitive decline, by improving brain neurotransmitters. [ 112 ]…”
Section: G Biloba and Covid‐19mentioning
confidence: 99%